untitled - Roberts, Matana (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Matana Roberts is a saxophonist, composer, and artist. In this open letter—and call to action—she describes the intergenerational trauma that has resulted from the history of white supremacy and police violence against persons of African descent, and reminds us how race and racism are intimately linked to health in myriad ways.